2017
DOI: 10.3389/fnins.2017.00262
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear Analysis of Scalp EEG by Using Bispectra: The Effect of the Reference Choice

Abstract: Bispectral analysis is a signal processing technique that makes it possible to capture the non-linear and non-Gaussian properties of the EEG signals. It has found various applications in EEG research and clinical practice, including the assessment of anesthetic depth, the identification of epileptic seizures, and more recently, the evaluation of non-linear cross-frequency brain functional connectivity. However, the validity and reliability of the indices drawn from bispectral analysis of EEG signals are potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 100 publications
(188 reference statements)
1
31
0
1
Order By: Relevance
“…It is possible that due to these limitations, there was no effect of AVG or REST procedures on the desired experimental changes in MMN amplitude and latencies. It should be noted however, that recent simulation and real EEG studies have reported the effectiveness of REST for the analysis of non-linear features of EEG data for montages with 21 channels (Chella et al, 2017 ). To our knowledge, this is the first empirical investigation of comparing the effects of three commonly used referencing procedures on experimental effects on auditory MMN.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible that due to these limitations, there was no effect of AVG or REST procedures on the desired experimental changes in MMN amplitude and latencies. It should be noted however, that recent simulation and real EEG studies have reported the effectiveness of REST for the analysis of non-linear features of EEG data for montages with 21 channels (Chella et al, 2017 ). To our knowledge, this is the first empirical investigation of comparing the effects of three commonly used referencing procedures on experimental effects on auditory MMN.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research in search of a gold standard referencing procedure for EEG/ERP research have determined that the potential at mastoid electrode sites used for referencing is non-zero (Yao, 2001 , 2017 ; Chella et al, 2017 ). When the EEG data is re-referenced to LM, the non-zero potentials at mastoids may get added or subtracted to the potential at the active electrode in effect increasing or decreasing its amplitude.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a remarkable result considering the differences in methodological (and arbitrary) choices we used to harmonize the analysis pipelines of the aforementioned studies. For the biomarkers for which we failed to observe a significant effect (PLV and sdDTF) this failure could be indeed related to different signal processing pipelines regarding the epoch length 61 , the reference montage 62,63 , the different state of vigilance [64][65][66] , which could have affected the results.…”
Section: Discussionmentioning
confidence: 90%